INFLUENCE OF GLYCERYL POLYETHYLENE GLYCOL RICINOLEATE (GPEGR) ON PRODUCTION PERFORMANCE OF BROILER CHICKEN - N. Dinesh Kumar; M. Ramachandran; K. Ayyappan; C. Mehala (Indian Journal of Veterinary and Animal Sciences Research, 2025)
A biological trial was conducted to evaluate the effect of glyceryl polyethylene glycol ricinoleate (GPEGR) supplementation on the production performance in broiler chicken. A total of two hundred day-old broiler chicks were randomly assigned to five dietary treatments containing forty birds in each group with five replicates in each treatment group and thus constituting eight birds per replicate . The control group (C) received basal diet, T1 group received the basal diet and GPEGR, while the T2, T3, and T4 groups received GPEGR-supplemented diets with graded reductions in energy density by 20, 40, and 60 kcal/kg, respectively. All the birds were maintained under uniform and standard managemental conditions with access to ad-libitum feed and water. The study found that the final body weight and average daily gain (ADG) in the T1 group (1804.99 g and 50.21 g, respectively) were significantly (P<0.05) higher than the control group (1662.80 g and 46.16 g, respectively). While the energy reduced diets (T2, T3, T4) supplemented with GPEGR did not show significant improvements in body weight and ADG compared to the control. The cumulative and average daily feed as well as the feed conversion ratio (FCR), showed no significant (P>0.05) differences among the groups. It can be concluded that the feeding of GPEGR supplemented diet containing 3000 Kcal per kg enhanced the growth rate in broiler chicken